2016
DOI: 10.1038/srep31092
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia intercalated flower-like MoS2 nanosheet film as electrocatalyst for high efficient and stable hydrogen evolution

Abstract: Ammonia intercalated flower-like MoS2 electrocatalyst film assembled by vertical orientated ultrathin nanosheet on graphite sheethas been successfully synthesized using one-step hydrothermal method. In this strategy, ammonia can effectively insert into the parallel plane of the MoS2 nanosheets, leading to the expansion of lattice and phase transfer from 2H to 1T, generating more active unsaturated sulfur atoms. The flower-like ammoniated MoS2 electrocatalysts with more active sites and large surface area exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 56 publications
2
57
0
Order By: Relevance
“…The methodology developed in this study can be applied to other types of nano-dimensional materials in addition to 2D materials. , and the samples in our work (red) [46][47][48][49][50][51][52][53][54][55][56]…”
Section: Discussionmentioning
confidence: 98%
“…The methodology developed in this study can be applied to other types of nano-dimensional materials in addition to 2D materials. , and the samples in our work (red) [46][47][48][49][50][51][52][53][54][55][56]…”
Section: Discussionmentioning
confidence: 98%
“…In this context, nanostructures of MoS 2 , amorphous 79 /crystalline, 1013 and vertically aligned structures 14,15 have been explored to maximize the number of active edge sites. MoS 2 is also hybridized with conducting/semiconducting/magnetic materials (graphene 1519 /CoSe 2 20 /CoS 2124 /CdS 25,26 /Fe 3 O 4 27 ) to enhance the catalytic activity through synergetic coupling effects. Metastable, intrinsically metallic, octahedral 1T MoS 2 obtained through exfoliation of trigonal prismatic 2H MoS 2 has proven to be an excellent catalyst for H 2 evolution reactions as the 1T phase facilitates electrode kinetics by increasing the electric conductivity and proliferation of the catalytic active sites.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 A weak peak at 9 was observed instead of the (002) peak at 14 for MoS 2 -CTAB, MoS 2 -SDS and MoS 2 -SDBS as compared to the pristine 2H-MoS 2 . This indicated that the (002) peaks moved forward, which was attributed to the increase in the interlayer spacing caused by the addition of surfactants, 19,20 demonstrating that there were few stacking layers of MoS 2 . On the whole, the effects of the three surfactants on the crystalline form and intensities of MoS 2 -X in the hydrothermal reaction were slight, and all the MoS 2 exhibited poor crystallinity, consistent with the previous results of the synthesis of MoS 2 using the hydrothermal method.…”
Section: Xrd Resultsmentioning
confidence: 98%